Carlo Martini: The Word of God in the Heart of Pastoral Life (Teología, 2017)
On the fifth anniversary of Cardinal Carlo M. Martini’s death (2012-2017), the author presents a brief sketch of his theological-pastoral biography focused on God’s Word. Despite the fact that his spiritual writings have been spread worldwide, there is no comprehensive reception of his thoughts during lifetime yet. This is aimed at providing insights into such aspect, thus suggesting two moments: to remember his jesuitical, biblicist and pastor’s figure, through significant experiences; and to rediscover the important parts of his teaching, considering a Church that allows itself to dream from a Gospel standpoint and deal with challenges of current times. A wide range of topics are displayed: contemplative life, primacy of the Word, eucharist centrality, missionary dimension, neighbors in society, dialogue with judaism, islam, and non believers, distinguishing the prolife of one of the greatest figures of the Church.
Keywords: Word of God; Pastoral; Lectio Divina; Dialogue; Judaism; Non-believer